A Method for Endurance Testing of Enameled Round and Rectangular Wires for Motors Controlled by SiC-based Inverters; IEEE Transactions on Dielectrics and Electrical Insulation; Vol. 28, iss. 6 - Gavrilenko V. A. Veronika Andreevna; Leonov A. P. Andrey Petrovich; Bukharkin A. A. Andrey Andreevich; Hlioui S. Sami; Lefebvre S. Stephane (2021, 2021)
Title screen